Lipidomics Changes in a Murine Model of Neuropsychiatric Lupus - Wang Y; Ren Y; Hong T; Lu D; Zhang F; Cao Y; Wang X (Dove Medical Press, 2022)
Yihan Wang,1,* Yating Ren,1,* Tao Hong,1 Dingqi Lu,2 Fan Zhang,2 Yi Cao,3 Xinchang Wang4 1Second Clinical Medical College, Zhejiang Chinese Medical University, Hangzhou, People's Republic of China; 2First Clinical Medical College, Zhejiang Chinese Medical University, Hangzhou, People's Republic of China; 3Department of Dermatology, The First Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, People's Republic of China; 4Department of Rheumatology, The Second Affiliated Hospital, Zhejiang Chinese Medical University, Hangzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Xinchang Wang, Department of Rheumatology, The Second Affiliated Hospital, Zhejiang Chinese Medical University, Hangzhou, Zhejiang Province, People's Republic of China, Tel +86 0571-85288249, Email ossani@126.comPurpose: Neuropsychiatric lupus (NPSLE) is one of the important manifestations of systemic lupus erythematosus. Previous studies mainly focused on the disruption of the blood-brain barrier and the production of brain-reactive autoantibodies, However, there is no comprehensive lipidomic analysis in NPSLE. Therefore, this research evaluated the lipidomic analysis in the hippocampus and liver of NPSLE mice with mood disorders, to explore the influence of the liver-brain axis on this disease.Methods: MRL/lpr mice and MRL/mpj mice were respectively used as NPSLE and control groups. Behavioral tests and systemic disease characteristics of mice were assessed at the age of 18 weeks. Ultra-Performance Liquid Chromatography-Tandem Mass Spectrometry (UPLC-MS/MS) was used for lipid metabolite determination. Multivariate statistical analysis was used to identify lipid metabolites that were differentially expressed in two groups.Results: Our results showed that 355 and 405 lipid metabolites were differentially expressed between the NPSLE and control groups in the hippocampus and liver. According to the pathway enrichment analysis, several pathways were affected, and the glycerophospholipid metabolism pathway was most relevant to the mouse's depressive behavior.Conclusion: Based on UPLC-MS/MS, the results provide evidence for how the liver-brain axis affects NPSLE and improve the understanding of NPSLE pathogenesis.Keywords: neuropsychiatric systemic lupus erythematosus, liver-brain axis, hippocampus, depressive behavior